Comparison of two kinds of lasers in the treatment of acne scars - Reinholz, Markus; Schwaiger, Hannah; Heppt, Markus V.; Poetschke, J.; Tietze, J.; Epple, Andreas; Ruzicka, T.; Kaudewitz, P.; Gauglitz, Gerd G. (Facial plastic surgery, 2015)
Acne scars are common and stigmatizing for the affected patients. Besides surgery, chemical peels, microdermabrasion, and microneedling, the treatment with fractional laser is a standard therapy. The results of reducing acne scars treated either with a fractional Er:YAG (erbium-doped yttrium-aluminum-garnet [Er:Y3Al5O1]) or a carbon dioxide (CO 2 ) laser at different wavelengths were compared and evaluated in the pilot study presented here. Fourteen patients with severe scars on both cheeks were treated four times in a random split-face approach: on one side with Er:YAG laser and on the contralateral side with CO2 laser following a standardized protocol. Therapeutic success was evaluated through the use of a high-resolution, 3D small-field capture system (PRIMOS), digital photography, and the Patient and Observer Scar Assessment Scale (POSAS) questionnaire. The evaluation was performed by a blinded investigator. Treatment results displayed a higher efficacy of the fractional CO2 laser compared with the Er:YAG laser as displayed by digital photographs. Additionally, objective (high-resolution, 3D small-field capture; PRIMOS) and subjective (POSAS) measuring results correlated positively in certain qualities (color, stiffness, thickness, surface, overall opinion). Using a novel scientific approach, we evaluated the therapeutic efficacy of different fractional lasers on acne scars using a rater-blinded approach. Compared with an Er:YAG laser, better skin smoothening was achieved by fractional CO2 laser treatment.